2021
DOI: 10.1055/a-1488-5625
|View full text |Cite
|
Sign up to set email alerts
|

Überprüfung der Kompetenzen von Notfallsanitätern – Umfragestudie zu Umsetzung und Rahmenbedingungen durch Ärztliche Leiter Rettungsdienst

Abstract: Zusammenfassung Hintergrund Eine Kompetenzüberprüfung von Notfallsanitätern (NFS) ist durch die Ärztlichen Leiter Rettungsdienst (ÄLRD) empfohlen. Die Umsetzung erfolgt individuell im Rettungsdienstbereich. Ziel der Studie ist die Beschreibung der aktuellen Situation als Diskussionsbeitrag für Weiterentwicklungen. Methode In der Zeit von Sept. 2019 bis Mai 2020 wurden die ÄLRD zu ihren … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
0
0
1
Order By: Relevance
“…As a monocentric study, it cannot be assumed that the results represent every rescue service location in Germany. As mentioned above, there are major differences in terms of training and organization (25). Nevertheless, we believe that the results of our study can be used to prioritize training evaluation in order to describe the local situation.…”
Section: Limitationsmentioning
confidence: 70%
See 3 more Smart Citations
“…As a monocentric study, it cannot be assumed that the results represent every rescue service location in Germany. As mentioned above, there are major differences in terms of training and organization (25). Nevertheless, we believe that the results of our study can be used to prioritize training evaluation in order to describe the local situation.…”
Section: Limitationsmentioning
confidence: 70%
“…In previous studies, we found that there were very different instructions regarding the implementation of training, testing and recommendations for the professionals (10,11). This heterogeneous practice in each district shows that there is no standard yet.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Ostmeier etal. habenineiner Befragung von ÄLRD gezeigt, dass meistens Fallszenarien als "Zertifizierung" oder Kompetenzcheck eingesetzt werden und auch für am sinnvollsten erachtet werden [37]. In welcher Form das Wissen überprüft wird (schriftlich, praktisch, mündlich), ist letztlich unerheblich, solange der Anwender und die Organisation eine definierte Überprüfung vorweisen können und die Ergebnisse die Standards einer guten Patientenversorgung widerspiegeln.…”
Section: Merke Zuletzt Gilt Es Dieunclassified